The influence of luxury brand selfies on luxury brand preference - Zalfa, Velian; Rufaidah, Popy (Manajemen dan Bisnis, 2025)
In today’s digital era, the growing phenomenon of luxury brand selfies has sparked interest in understanding their impact on consumer attitudes. This study explores how sharing selfies featuring luxury brands on social media influences consumers’ preferences toward those brands. Employing a quantitative approach, data were collected through an online survey distributed to 225 respondents who had purchased luxury brands and actively shared brand-related selfies. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the research tested the effect of three dimensions—narcissism, materialism, and selfie posting behavior—on luxury brand preference. The findings reveal that among the three variables, only materialism significantly affects luxury brand preference. In contrast, narcissism and selfie-posting behavior show no meaningful influence. This suggests that highly materialistic individuals are more likely to prefer luxury brands, as these brands align with their desire for symbolic status. The study provides insight into consumer-brand interaction in the digital space. It encourages future research to include additional psychological or cultural variables to better understand brand-related behavior in online environments.